Production and Purification of Xylanase From Indonesian Isolate Bacillus sp. AQ-1 Grown on Bunch Palm Oil - PUJI RAHAYU; SISWA SETYAHADI; . HARMITA (Indonesian Society for microbiology, 2009)
Xylanase (endoxylanase, EC 3.2.1.8) is a commercial enzyme that has been applied in the industrial production of fuel, food, textiles and paper. Xylanase was isolated from the culture supernatant of Bacillus sp. AQ-1 grown on Nakamura medium containing 0.5% powder bunch palm oil. The optimum pH and temperature of xylanase activity were pH 7.0 and 60 °C, respectively. The enzyme was purified by anion exchange chromatography using DEAE-Sepharose-Fast-Flow column and gel filtration chromatography using Sephacryl S-300 column. The results showed that purification of xylanase produced two forms of xylanase, which were identified as xylanase A and xylanase B. Xylanase A can be separated from xylanase B by ultrafiltration using a 30 kDa polyethersulfone membrane. The molecular weight of xylanase A and B were 15.7 and 57.7 kDa, respectively.